Antimicrobial Therapy in Preventing Wound Infection Following Appendicectomy in Uncomplicated Appendicitis: A Comparative Study Between Single Dose And Multiple Doses In Adults (Journal of Surgical Sciences, 2019)
Objectives: To find out the efficacy of single dose antibiotic vs multiple dosesin preventing wound infection following appendicectomy for uncomplicated appendicitis.Methods: A prospective comparative study was conducted in the Department of Surgery, Chittagong Medical college Hospital from January'2009 to June'2009. 100 patients with uncomplicated appendicitis who underwent appendicectomy during that period were included in this study. Among them 50 cases were included in study group ·(SG) who were given only single dose of combination drugs ( lnj. Cefuroxime + lnj. Metronidazole).ln rest of the 50 cases (CG), antibiotics were continued for 7 days postoperatively.Result: Maximum incidence of acute appendicitis was in the 2nd and 3rd decade of life with male preponderance .Rate of wound infection in the study group and control group was 4% and 2% respectively which was not statistically significant .The duration of antibiotic therapy had no significant effect on the length of hospital stay between the two groups ; 2.48 days vs 2.9 days [mean + s.d. 69.6 # 16.8 hours ] in the study and control group respectively, though treatment cost was higher in control group in comparison to the study group .Conclusion: Single dose of preoperative antibiotics is adequate for prevention of postoperative wound infection following appendicectomy for uncomplicated appendicitis.Journal of Surgical Sciences (2015) Vol. 19 (1) : 17-20